The Hedonic and Sensoric Quality of Prerigor and Postrigor Rabbit Meatballs With Addition of different levels of of Starch and Sago Flour Combination - . Farida; E. Abustam; S. Kadir (Jurnal Ilmu dan Teknologi Peternakan, 2012)
Meatballs product quality significantly affects the consumer preferences.  Meat and other ingredients are very important in determining meatballs product quality.   Processing of rabbit meat with sago flour is intended to substitute the use of starch flour that has been used so far. The aim of the research was to determine the hedonic and sensory quality of flavor, taste and colour of rabbit meatballs with addition of different levels of starch and sago flour combination. The experiment was performed by factorial arrangement (2x5) according to completely randomized design. The first factor was the condition of rigor (prerigor and postrigor) and the second factor was the combination of starch and sago flour (30% starch, 30% sago, 15% starch + 15 % sago, 20% starch + 10% sago and 10% starch + 20% sago). Replication for each treatment combination was three. Sensory and hedonic properties observed were the aroma, flavour and color of rabbit meatballs. The results showed that the rigormortis condition of meat affected the quality of rabbit meatballs in terms of flavour dan colour. Addition of combination of starch and sago flour at different level significantly affected flavour, taste and colour of the rabbit meatballs. There was an interaction effect of rigormortis condition and the combination starch or sago levels on the color of rabbit meatballs. In conclusion, the best meatballs quality obtained on the use of prarigor meat with addition of combination 15% starch + 15% sago.